Pengaruh Bilas Lambung NACL 0,9% Terhadap Status Hemodinamik Pada Pasien Stres Ulcer Dengan Post Craniotomy Atas Indikasi Cidera Kepala Berat Di Ruang Intensif Rumah Sakit Umum Daerah Dr. Moewardi Surakarta - Astrini Rachma Putri; Rita Benya Adriani ((JKG) Jurnal Keperawatan Global, 2017)
Abstract: Gastric Lavage, Ulcer Stress, Hemodynamic Status. Severe injury on head with post-craniotomy in the intensive room needs tight supervisory related to the pressure of intracranial in which can produce risk of physiological stress, i.e. acute gastrointestinal bleeding (ulcer stress) which can disturb the hemodynamic status (MAP, artery). One of therapies which can be applied is gastric lavage. This pupose to know the effect of gastric lavage of NaCl 0.9% to the status of hemodynamic to the patient of ulcer stress with post-craniotomy by the indication of severe injury on head in the intensive room of Dr. Moewardi Hospital in 2015. This research is experimental research by cross sectional design for 30 patients with ulcer stress of post-craniotomy by the indication of severe injury on head and treated with gastric lavage of NaCl 0.9% in the ICU and HCU of Dr. Moewardi Hospital during March-April 2015. The statistical analysis applied is Paired Sample T-Test. According to statistical test, the result of t MAP 4,033 with the value of p 0,000 and the artery result of 4,359 with the value of p 0,000, in which t table is 2.045 and the criteria of p < 0.05. Thus, the value of th MAP > tt, th artery > tt, and the result of MAP p 0,000 (<0.05) and artery p 0,000. There is a meaningful influence to the hemodynamic status in the ulcer stress patient with with post-craniotomy by the indication of severe injury on head who is treated with gastric lavage of NaCl 0.9%.